TiOx/Ti/TiOx Tri-Layer Film-Based Waveguide Bolometric Detector for On-Chip Si Photonic Sensor - Shim, Joonsup; Lim, Jinha; Geum, Dae-Myeong; You, Jong-Bum; Yoon, Hyeonho; Kim, Joon Pyo; Baek, Woo Jin; Han, Jae-Hoon; Kim, Sanghyeon (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
In this article, we experimentally demonstrate an on-chip optical power monitoring at the near-infrared spectral region (1520-1600 nm) using the waveguide bolometric detector with a TiOx/Ti/TiOx tri-layer film based on the silicon-on-insulator (SOI) platform. For the incident light absorption causing a heat generation, a heavily doped (n(+)) Si waveguide is introduced to utilize the mechanism of free-carrier absorption (FCA), and a metal (Au) strip is deposited onto the n(+) Si waveguide to further enhance the light absorption. A bolometric material of TiOx/Ti/TiOx tri-layer film is integrated for the thermal-to-electrical conversion. As a result, it exhibits superior performances, which are the temperature coefficient of resistance (TCR) of -2.296%/K and the maximum sensitivity of -46.45%/mW with a low wavelength-dependency. In addition, a rapid response time is obtained with the rise/fall time of 24.6 mu s/29.8 mu s, which is enough for a variety of optical sensing applications. This work demonstrates the waveguide-based bolometric photodetection using the FCA effect, for the first time to our knowledge, which can also be simply extended for the operation wavelength range to the mid-infrared (MIR) spectral region for bio/chemical sensing applications.